Generation of Functional, Antigen‐Specific CD8+ Human T Cells from Cord Blood Stem Cells Using Exogenous Notch and Tetramer‐TCR Signaling. (3rd January 2014) - Fernandez, Irina; Ooi, Tracy P.; Roy, Krishnendu
Abstract: In vitro differentiation of mouse and human stem cells into early T cells has been successfully demonstrated using artificial Notch signaling systems. However, generation of mature, antigen‐specific, functional T cells, directly from human stem cells has remained elusive, except when using stromal coculture of stem cells retrovirally transfected with antigen‐specific T cell receptors (TCRs). Here we show that human umbilical cord blood (UCB)‐derived CD34+CD38−/low hematopoietic stem cells can be successfully differentiated into functional, antigen‐specific cytotoxic CD8+ T cells without direct stromal coculture or retroviral TCR transfection. Surface‐immobilized Notch ligands (DLL1) and stromal cell conditioned medium successfully induced the development of CD1a+CD7+ and CD4+CD8+ early T cells. These cells, upon continued culture with cytomegalovirus (CMV) or influenza‐A virus M1 (GIL) epitope‐loaded human leukocyte antigen (HLA)‐A*0201 tetramers, resulted in the generation of a polyclonal population of CMV‐specific or GIL‐specific CD8+ T cells, respectively. Upon further activation with antigen‐loaded target cells, these antigen‐specific, stem cell‐derived T cells exhibited cytolytic functionality, specifically CD107a surface mobilization, interferon gamma (IFNg) production, and Granzyme B secretion. Such scalable, in vitro generation of functional, antigen‐specific T cells from human stem cells could eventually provide a readily available cell source for adoptive transfer immunotherapies and also allow better understanding of human T cell development. Stem Cells 2014;32:93–104